Loads on Lower Limb Joints and Optimal Action of Muscles for Shock Reduction - WANG, Yongjin; MATSUHISA, Hiroshi; HONDA, Yoshihisa (Transactions of the Japan Society of Mechanical Engineers Series C, 1998)
In this paper, a new method was proposed to theoretically analyze the forces on the toe, ankle and knee joint using a musculoskeletal model of lower limb. It was shown that the maximum force on the knee joint when a human jump down vertically from a height of 0.3 meter could come up to 11.2 times of his weight without an active movement of shock absorbing. Moreover, the optimal movement of lower limb muscle during a vertical landing on a hard surface was proposed to be solved by converting the multi dimentional and monlinear optimal control problem to a parameter optimazation problem. Detail investigations were performed in three cases when minimize the forces on the toe, on the ankle and on the knee joint, respectively. By using this optimal movement, it is possible to reduce the forces on the toe and knee joint by half. It was made clear from the optimization result that it is more appropiate to use the forces on the toe as an object function. Furthermore, it was found that the force on the toe and the activation level of lower limb muscle predicted by parameter optimization agreed well with the experimental results.